(untitled) (LACCEI, 2024)
In the last times, the slaughter plants have been forced to implement adequate stunning techniques prior to slaughter, in order to guarantee the quality of the meat destined for human consumption and animal welfare. In view of this, the present systematic review is aimed at collecting scientific theoretical information on the different types of stunning techniques and methods used by the slaughter plants. For that, the search for scientific theoretical information was carried out in the information sources of: Scopus, ScienceDirect, ProQuest, Ebsco and Scielo including studies carried out over the last 10 years such as: research articles, review articles, scientific journals, academic publications, open access files, obtaining a total of 216 articles, of which a qualitative analysis was carried out to determine which articles provided a response the research question obtaining 61 articles, of these the vast majority talk about the use of electrical stunning (ES) by means of water baths, and a smaller number of ammunition to controlled atmosphere stunning (CAS) or also known as modified atmosphere (KAPS). ), the same ones that use gas mixtures and low atmospheric pressure (LAPS).